2004
DOI: 10.1262/jrd.50.515
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin Gene Expression in Mouse Placenta during the Latter Half of Pregnancy

Abstract: Abstract. Gene expressions and their interaction are complex and have not been definitely clarified in the placenta. To identify interactions of gene products previously not studied, we applied cDNA subtraction analyses to the placenta between days 12 and 16, days 12 and 14, days 14 and 16 of pregnancy. Among subtracted cDNAs cathepsin M, Q and R in PECs were specifically identified on days 14 and 16 pregnancy. All of these gene expressions exhibited a similar pattern to the mPL-II gene expression determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Creg1 inhibits cell growth dependent on Igf2R, and this suggests that i n t e r a c t i o n s b e t w e e n C r e g 1 a n d a w e l lcharacterized placental growth factor may contribute to regulation of proliferation and differentiation in multiple lineages. Furthermore, Igf2 has been found to interact with cathepsin, which has been identified as a specific gene related to mPL-II synthesis, using the subtracted cDNA libraries in our previous work [12]. It has also been reported that lysosomal enzyme cathepsin D and Igf2, which share a common Igf2 / mannose-6-phosphate (M6P) transmembrane receptor, are synthesized and secreted by breast cancer cells.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Creg1 inhibits cell growth dependent on Igf2R, and this suggests that i n t e r a c t i o n s b e t w e e n C r e g 1 a n d a w e l lcharacterized placental growth factor may contribute to regulation of proliferation and differentiation in multiple lineages. Furthermore, Igf2 has been found to interact with cathepsin, which has been identified as a specific gene related to mPL-II synthesis, using the subtracted cDNA libraries in our previous work [12]. It has also been reported that lysosomal enzyme cathepsin D and Igf2, which share a common Igf2 / mannose-6-phosphate (M6P) transmembrane receptor, are synthesized and secreted by breast cancer cells.…”
Section: Discussionmentioning
confidence: 90%
“…In our previous work, we studied specific gene expression related to mPL synthesis using cDNA subtraction analysis that specifically identified cathepsin family genes [12]. In the present study, we employed cDNA microarray analysis, which was expected to be more sensitive than cDNA subtraction analysis, for the detection of specific genes related to mPL gene expression, including angiogenetic genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the organization of different cell types in the labyrinth, we performed in situ hybridization and immunohistochemical analyses with probes and antibodies specific for trophoblast and fetal cell types. In situ hybridization for cathepsin q (Ctsq) (Ishida et al, 2004), a gene specific for mononuclear trophoblasts (also called sinusoidal trophoblast giant cells) (Simmons et al, 2007) showed that the maternal blood spaces are enlarged and disorganized in Sp1/Sp3 compound heterozygous and in Sp3 null placentae (Fig. 3D, Ctsq).…”
Section: Sp3 Null Micementioning
confidence: 99%